PENGARUH MEDIA SOSIAL INSTAGRAM @PESONAID_TRAVEL TERHADAP MINAT BERKUNJUNG KAUM MILENIAL PADA WISATA INDONESIA - Arlisa Intan Ainiyyah (2021)
This research is motivated by the development of communication technology, namely social media. Tourism can use social media as a visual promotion medium, namely the Instagram social media platform. One of the Instagram social media accounts that uses it is @pesonaid_travel which is managed directly by the Ministry of Tourism and Creative Economy of the Republic of Indonesia. This study aims to determine whether there is an influence of social media Instagram @pesonaid_travel on millennials' interest in visiting Indonesian tourism and the magnitude of the influence of social media Instagram @pesonaid_travel on millennials' interest in visiting Indonesian tourism. the population in this study there are followers of the @pesonaid_travel account, with a sample of 100 respondents. This study uses quantitative methods with the type of explanatory research. From the results of the analysis of this study, based on the correlation test, there is a strong relationship between the X and Y variables of 0.744. And obtained R square that is equal to 57.30% and from the results of a simple linear regression test that is getting the results Y = 3.895 + 0.388 X and the results of the hypothesis test that is the value of tcount 11.022 > ttable 1.660. It can be concluded that there is an influence of the Instagram @pesoanid_travel social media account on visiting interest. It can be concluded that there is an influence between variable X (social media Instagram @pesonaid_travel) on variable Y (millennials' interest in visiting Indonesian tourism).